2016
DOI: 10.1038/s41559-016-0010
|View full text |Cite
|
Sign up to set email alerts
|

Multicopy plasmids potentiate the evolution of antibiotic resistance in bacteria

Abstract: Plasmids are thought to play a key role in bacterial evolution by acting as vehicles for horizontal gene transfer, but the role of plasmids as catalysts of gene evolution remains unexplored. We challenged populations of Escherichia coli carrying the bla β-lactamase gene on either the chromosome or a multicopy plasmid (19 copies per cell) with increasing concentrations of ceftazidime. The plasmid accelerated resistance evolution by increasing the rate of appearance of novel TEM-1 mutations, thereby conferring r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
246
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 182 publications
(256 citation statements)
references
References 61 publications
10
246
0
Order By: Relevance
“…However, in the absence of antibiotics, an increase in the PCN usually produces an increase in the fitness cost produced by a plasmid (10,15). To analyze this possibility we determined the biological cost of the different plasmid alleles alone and cohabiting using the coefficient of selection (s) as previously described (11).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, in the absence of antibiotics, an increase in the PCN usually produces an increase in the fitness cost produced by a plasmid (10,15). To analyze this possibility we determined the biological cost of the different plasmid alleles alone and cohabiting using the coefficient of selection (s) as previously described (11).…”
Section: Resultsmentioning
confidence: 99%
“…Single mutations can give rise to new compatible plasmids that are able to coexist in the same cell, increasing the global PCN (7,8). These mutations have been widely described in vitro (9) and arise naturally by chance due to the high plasmid copy number exhibited by ColE1-like plasmids (10), but to the best of our knowledge, there are no natural examples of cohabiting ColE1 plasmids differentiated by only a single nucleotide polymorphism (SNP).…”
mentioning
confidence: 99%
“…This result supports other studies showing that the deletion of iterons increased plasmid copy number of theta plasmids (reviewed in [89, 90]). For example, Millan et al [91] showed that mutations acquired in the OriV of a synthetic ColE1-like plasmid (pBGT) carrying bla TEM-1 β-lactamase gene increased plasmid copy number and subsequently increased ceftazidime resistance several folds.…”
Section: Discussionmentioning
confidence: 99%
“…Plasmids are widely distributed across prokaryotes, and help bacteria adapt to a myriad of different environments, conditions, and stresses (3,4), playing a key role in bacterial ecology and evolution (5)(6)(7). The most vivid testimony to the power of plasmids as catalysts for bacterial adaptation is their role in the spread of antibiotic resistance among clinical pathogens (8), which has emerged as a major health problem over the past decades (9).…”
Section: Introductionmentioning
confidence: 99%